The Effectiveness of Supervision Over Dimensionand Over LoadTrucks in Bengkulu Province (Study on UPPKB Padang Ulak Tanding Bengkulu Province) - Bambang Hariyanto; Slamet Widodo; Trisna Murni (The Manager Review, 2021)
The current study aimed to determine the effectiveness of supervision, the causes of ineffectiveness and solutions to the empirical problem of ODOL trucks at UPPKB Padang Ulak Tandaing. Qualitative approaches and in-depth interview methods were used to collect data. Drivers, BPTD officials, and UPKKB personnel became the informants of this research. Data were collected from 16 informants involved in the process of monitoring ODOL trucks at UPPKB Padang Ulak Tanding. Descriptive analysis is used to describe the results of interviews and documentation from informants. The results of the research show that: (1) the percentage of the results of measuring the effectiveness of supervision based on the process reaches 78%, which means it is quite effective; (2) The inhibiting factors for supervision, namely the condition of human resources are not yet ideal and the implementation of work standards is not perfect, internal control is weak, law enforcement  is weak, legalawareness of owners of freight transport is weak and facilities/infrastructure are not adequate; (3) Efforts to overcome the empirical problem of ODOL trucks include the recruitment of specializations for motor vehicle testers, the leadership must be a role model for subordinates, the application of rewards/punishments for the performance of investigators, the implementation of a legal awareness campaign and the provision of inadequate facilities/infrastructure. Discussions, implications and recommendations are presented.